Capacity Enhancement for the Vehicular Network using Spatial Multiplexing - Hadi Saleh, Hassan; Talib Hasoon, Saad (International Journal of Engineering and Technology, 2018)
Vehicular Ad hoc Network (VANET) is an advanced system and subcategory of a Mobile Ad hoc Network (MANET), it has as the potential to significantly impact road safety and improve traffic by providing critical information to drivers on critical routes. The system can inform the driver of a local anomaly, which is a very short distance from the sensors. Data from this sensors can be passing between vehicles so as to increase awareness of this environment. Intelligent Transport System (ITS) applications will include traffic efﬁciency, comfort of driving and road safety. The transaction of warning messages exploits a limited capacity because these applications generate little separate messages. Estimating the capacity of the VANET is therefore essential, as it may limit the deployment or usefulness of these applications. Therefore, an estimate must be made in advance for application design with capacity limitations in mind. VANET capacity is limited mainly through spatial reuse.  Multiple-Input Multiple-Output (MIMO) structures have been suggested to replace the conventional systems. In MIMO systems, a much higher data rate can be achieved than in a VANET environment. The objectives of the paper to study the capacity of the VANET network associated with new promising MIMO technology. Spatial multiplexing (SM),utilizes the spatial dimension to maximizethe capacity of a link without expanding a bandwidth. The SM gain is achieved throughtransmitting signals concurrently on parallel channels spatially with the same frequency. Capacity calculated over VANETs environments with MIMO/SM techniques, using Rayleigh Fading Channel with BPSK modulation. The results of MATLAB simulation package 2017a, indicate the enhancement in the unit of bit per second per Hertz (b/s/Hz). A maximum capacity improvement for MIMO system over Single Input Single Output (SISO) was achieved by using (4 x 4) system, it is about 16.14 b/s/Hz.
Keywords: VANET; MIMO; Spatial Multiplexing; Channel Capacity.